Perbedaan Pengaruh Latihan Cycle Ergometry Dan Senam Zumba Terhadap Pengoptimalan Vo2max Pada Mahasiswi Fisioterapi STIKes Baiturrahim - Hadi, Putra; Faridah, Faridah; Sari, Indah Permata (Jurnal Akademika Baiturrahim Jambi, 2024)
For female students, physical fitness is very important to support, facilitate, launch their lecture activities and the success of female students in learning is influenced by ability, willingness, nutritious food, and good body condition. Good body condition if the level of aerobic endurance is good which can be obtained by doing regular sports activities. Maximum oxygen consumption (VO2Max) is a physiological parameter that defines a person's aerobic capacity. Increasing VO2Max cannot be achieved easily, but must be done through intensive training with a good training program based on correct exercise principles. The purpose of this study was carried out to find out whether there was a difference in optimizing the VO2Max value between groups following Cycle Ergometry and Zumba Gymnastics. This research was conducted on all female students in the second and fourth semesters of the DIII Physiotherapy Study Program at the Baiturrahim Jambi STIKes. This type of research used a quasi-experimental with two groups pre and post test design, group A was given Cycle Ergometry and group B was given the Zumba Gymnastics treatment. The two groups will take measurements before and after the treatment 3 times a week for 1 month. The research instrument was measured using a test, namely the Multistage Fitness Test (MFT), which was measured before and after. Analysis of the data collection used was the Shapiro Wilk test, paired sample t-test and independent sample t-test. In the paired sample t-test the Cycle Ergometry and Zumba Gymnastics group had Sig. (2-tailed) 0.00<0.05. Whereas in the independent sample t-test the results of Sig. (2-tailed) on Equal variances assumed is 0.45<0.50 and Equal variances not assumed is 0.47<0.50 The conclusion of this research is that there are differences in the results of the two treatments.